Study on formability and dislocation density in forming of hemispherical cup. (2020) - Vignesh, G.; Pandivelan, C.; Sathiya Narayanan, C.
Abstract: The aim of this work is to study formability and dislocation density in the plastically deformed cup by both punch and die forming process and single point incremental forming (SPIF) process. The stainless steel grade 202 (SS 202) sheet metal was used for this study. The formability from forming limit diagram (FLD) and dislocation density by X-ray diffraction line profile analysis (XRDLPA) were determined for the cup formed by both forming processes and compared with each other. The amount of strain induced transformation (SIT) was also found from microstructure for the cup formed by both forming processes and compared. The cup with hemispherical shape was formed by SPIF process and its amount of deformation and dislocation density was also found.